Public procurement of paddy in Bangladesh: Implications for policy - Ahmed, Akhter; Bakhtiar, M. Mehrab; Anowar, Md Sadat; Rahman, Mohammad Moshiur (Bangladesh Institute of Development Studies, 2021)
Public procurement of foodgrains in Bangladesh has significant implications for production and public foodgrain stock. Boro is the main rice crop cultivated in Bangladesh. During the 2019 boro harvest season, farmers in Bangladesh, particularly smallholder farmers, were adversely affected by low paddy prices. This paper assesses to what extent boro farmers could sell their paddy to the government, evaluates the efficacy of direct paddy procurement from farmers and examines options for improving Bangladesh’s foodgrain procurement system. Relevant actors in the boro paddy procurement system were inter- viewed, including boro-growing farm households, rice millers, traders, and government officials. We have also conducted a study in West Bengal, India, to explore alternative paddy procurement systems. Using evidence from Bangladesh and West Bengal, we propose two options for rice procurement in Bangladesh. First, when the paddy price is low and does not cover farmers’ production cost per unit, the government can purchase paddy directly from farmers to provide necessary price support. Second, when the paddy price is high, the government can purchase rice from the market through open tender to build or replenish public foodgrain stocks.